O-029 Ace aspiration is a safe and effective first-line treatment for acute ischemic strokes in the anterior circulation. (23rd July 2017) - Almandoz, Delgado J; Kayan, Y; Young, M; Scholz, J; Milner, A; Fease, J; Roohani, P; Wallace, A; Mulder, M; Tarrel, R
Abstract : Purpose: To evaluate the effectiveness of the Penumbra system with ACE reperfusion catheters only (ACE only) versus ACE followed by Solitaire stent-retriever rescue (Solumbra rescue) for the treatment of anterior circulation emergent large vessel occlusions (ELVOs). Methods: We performed a single center, retrospective review of 100 consecutive patients with anterior circulation ELVOs treated with ACE as first-line therapy. If successful revascularization (TICI 2b-3) was not achieved with ACE only, then Solumbra rescue was utilized. Baseline characteristics, procedural variables, and modified Rankin Scale (mRS) at 90 days were recorded. Results: 84 patients were treated with ACE only and 16 patients required Solumbra rescue. 53 patients received iv-tPA prior to mechanical thrombectomy. Overall successful revascularization for all 100 consecutive patients was 90%, with puncture to reperfusion time of 38.7 min, embolization to new territory rate of 5%, and post-procedure symptomatic intracranial hemorrhage rate of 3% (2 subarachnoid, 1 intraparenchymal). Successful revascularization using ACE only was achieved in 78 patients (38 after a single pass), while 12 of the 16 patients requiring Solumbra rescue were successfully revascularized (75%). Puncture to reperfusion time for ACE only versus Solumbra rescue were 30.5 and 81.8 min, respectively (p<0.0001). A good clinical outcome, mRS 0–2 at 90 days, was achieved in 46% (46/100) of patients, including 49% (41/84) of patients treated with ACE only and 31% (5/16) of patients requiring Solumbra rescue. There was a statistically-significant difference in the rate of successful revascularization with ACE only as well as Solumbra rescue rate between the first 20 and subsequent 80 cases (Table 1). Successful revascularization with ACE only was achieved in 64% of patients treated with ACE 60, 88% with ACE 64, and 100% with ACE 68 (p<0.001, Table 2). One-pass successful revascularization rate was 31% with ACE 60, 38% with ACE 64, and 50% with ACE 68 (p=0.09). Mean puncture to reperfusion time was 49 min with ACE 60 and 30 min with ACE 64/68 (p=0.002). The Solumbra rescue rate was 29% in patients treated with ACE 60, 3% with ACE 64 and 0 with ACE 68 (p=<0.001). Conclusion: Aspiration thrombectomy using the Penumbra system with ACE reperfusion catheters is an effective first-line treatment for anterior circulation ELVOs, with the option to use adjunctive stent-retriever devices if aspiration alone is not sufficient. Advancements in reperfusion catheter technology from ACE 60 to ACE 68 have resulted in shorter procedural times and reduced need for adjunctive stent-retriever device use. Disclosures: J. Delgado Almandoz: 2; C; Penumbra, Inc, Medtronic Neurovacular. Y. Kayan: 2; C; Penumbra, Inc, Medtronic Neurovacular. M. Young: None. J. Scholz: None. A. Milner: None. J. Fease: None. P. Roohani: None. A. Wallace: None. M. Mulder: None. R. Tarrel: None.